Unsteady Flow Simulation and Combustion of Ethanol in Diesel Engines - Jan Labaj; Dalibor Barta (Communications - Scientific letters of the University of Zilina, 2006)
The paper presents the survey of ethanol application as the fuel for diesel engines which is added to diesel fuel or injected to the inlet manifold. The paper describes unsteady flow simulation in the inlet manifold of a 4 cylinder diesel engine with injected ethanol (Martin Diesel UR IV). The calculation of mixing rates is based on transient spray-plume-growth with concentration and temperature profile applying the CFD code (software of Fluent Inc. USA). The calculation of combustion was performed using a RNG kε (renormalization group) turbulent model, standard wall function and a PDF model for chemical equilibrium of gas composition and kinetics in the combustion chamber.